2013
DOI: 10.1111/1365-2478.12039
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of tensor gravity data using an adaptive tilt angle method

Abstract: Full Tensor Gravity Gradiometry (FTG) data are routinely used in exploration programmes to evaluate and explore geological complexities hosting hydrocarbon and mineral resources. FTG data are typically used to map a host structure and locate target responses of interest using a myriad of imaging techniques. Identified anomalies of interest are then examined using 2D and 3D forward and inverse modelling methods for depth estimation. However, such methods tend to be time consuming and reliant on an independent c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 18 publications
3
8
0
Order By: Relevance
“…It is shown that the scaling function plots of ridge1 and ridge2 of g xz andg yz are different ( Fig. The average depth of cap rock is about 200-300 m. The results are in agreement with previous research and the geologic information available (Oliveira and Barbosa 2013;Salem et al 2013;Geng et al 2014;Zhou 2015). Therefore, for the field FTG data, we need to calculate the average value of the seven scaling exponents.…”
Section: F I E L D D a T A P R O C E S S I N Gsupporting
confidence: 84%
See 1 more Smart Citation
“…It is shown that the scaling function plots of ridge1 and ridge2 of g xz andg yz are different ( Fig. The average depth of cap rock is about 200-300 m. The results are in agreement with previous research and the geologic information available (Oliveira and Barbosa 2013;Salem et al 2013;Geng et al 2014;Zhou 2015). Therefore, for the field FTG data, we need to calculate the average value of the seven scaling exponents.…”
Section: F I E L D D a T A P R O C E S S I N Gsupporting
confidence: 84%
“…Due to the needs of increased data volume and improved accuracy, several gravity and gravity gradient tensor data processing methods have recently been proposed. The adaptive tilt-depth method was used to interpret gradient tensor data, and satisfactory results were obtained with regard to accuracy (Salem et al 2013). Therefore, demand for the interpretation methods of gradient tensor data has increased in geologic research.…”
Section: Introductionmentioning
confidence: 99%
“…Different values of N should be chosen for different models before depth estimation (Salem et al, 2007(Salem et al, , 2013Cooper, 2011Cooper, , 2012Fairhead et al, 2011). However, in real potential field interpretation, the buried source type is unknown.…”
Section: Generalized Tilt-depth Methodsmentioning
confidence: 99%
“…Cooper (2012) generalized the method and applied it to gravity data depth estimation by identifying circular contours of the ratio of the vertical to the total horizontal derivative with sphere and vertical cylinder models. Salem et al (2013) added a scale value characterizing the source type into the equation of tilt angle to estimate the location and depth of simple buried gravity sources. However, these methods all need the prior information of the source type before calculating the buried depth.…”
Section: Introductionmentioning
confidence: 99%
“…Then, it was developed into the gradient tensor form to interpret gravity and FTG data by (ZHANG et al 2000). The same as Euler deconvolution method, Tilt-depth method also was modified to interpret FTG data (SALEM et al 2013). Analytic signal method for FTG data was established (BEIKI 2010).…”
Section: Introductionmentioning
confidence: 99%